PENGARUH PERILAKU HERDING, PENYESALAN INVESTASI, DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI KRIPTO PADA GEN Z - Tasya Tasya; Mortigor Afrizal Purba (SCIENTIA JOURNAL, 2026)
This study aims to analyze the influence of herding behavior, experienced regret, and financial literacy on cryptocurrency investment decisions among Generation Z in the Riau Islands. The research employs a quantitative approach, utilizing online questionnaires for data collection. A sample of 100 respondents was selected using the purposive sampling technique, and the data were analyzed using multiple linear regression in SPSS version 31. The results indicate that experienced regret and financial literacy have a significant positive effect on investment decisions. However, herding behavior does not show a significant partial effect. Simultaneously, all three independent variables together significantly influence cryptocurrency investment decisions. The study concludes that while social influence (herding) is not a primary driver, emotional learning from past experiences and cognitive financial understanding are crucial determinants in the investment decisions of Generation Z.